Aulacophora sp. (Coleoptera: Chrysomelidae) - a new pest on Som (Persea bombycina) and Soalu (Litsaea monopetala) in Kalimpong Hills (The Journal of Plant Protection Sciences, 2022)
Muga, the golden-yellow silk is obtained from  semi-domesticated silkworm called Antheraea  assamensis Helfer. Muga culture is an age-old  practice in the Brahmaputra valley of Assam.  However, in recent years production of muga  silkworm seed crops is adversely affected in  Assam with the rise of temperature due to  global warming. Kalimpong (latitude 27°06 N, longitude 88°47 E, 1247 m above msl) is one of the potential zones for production of muga  seed during June-July and August September  crop. Accordingly, primary food plant of  muga silkworm (Antheraea assamensis Helfer) viz. Som [Persea bombycina (King ex  Hook. f.) Kosterm] (Family: Lauraceae)] and  Soalu [Litsaea monopetala (Roxb) Pearson]  (Family: Lauraceae) has been raised in large  scale on the hilly terraces of Kalimpong. The  food plants are usually attacked by many  pests like shoot borer, trunk borer, leaf min ers, leaf galls, mealy bugs (3).
Keywords: relationship; symptoms; assamensis